A struggle for identity Muslim women in the United Provinces - Siddiqui, Firdous Azmat (Foundation Books, 2014)
In the nineteenth century, the British were occupied with the question of becoming socially acceptable, as they had already established political and military sway in India. It was in this context that the servants of the East India Company, merchants, adventurers and missionaries who arrived in India from Europe attempted to enter the zennana, in much the same manner as the ruling Indian elites. These foreigners adopted the ways of the ruling class, and thus demonstrated a preference for the Muslim section of Indian society. This book is an attempt to understand the social and economic profile of Muslim women in India and to shed light on the conditions of Indian Muslim women in the United Province particularly after 1857. This period is significant for Muslim society as it was undergoing social and economic transition especially with the Mughal dynasty reaching its end. Besides, the book critically discusses the influence of how the new colonial judicial system weakened traditional customs and questions whether this legal system was beneficial to Muslim women or whether it enhanced its complexities